The molecular mechanism of the effect of sulfur dioxide inhalation on the potassium and calcium ion channels in rat aortas. (April 2016) - Zhang, Q; Bai, Y; Yang, Z; Tian, J; Meng, Z
This study investigated the molecular mechanism of the effect of sulfur dioxide (SO2 ) on the expression of adenosine triphosphate (ATP)-sensitive potassium ion (K + ; KATP ) channel, big-conductance calcium ion (Ca 2+ )-activated K + (BKCa ) channel, and L-type (L-Ca 2+ ) channel subunits in rat aortas with quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot. The results showed that the messenger RNA and protein levels of the KATP channel subunits Kir6.1, Kir6.2, and sulfonylurea receptor 2B (SUR2B) of rat aortas were significantly increased by SO2 at 14 mg/m 3, whereas the levels of SUR2A were not changed. SO2 at all the treated concentrations markedly raised the expression of the BKCa channel subunits α and β1. SO2 at 14 mg/m 3 significantly decreased the expression of the L-Ca 2+ channel Cav 1.2 and Cav 1.3. The histological examination of rat aorta tissues showed moderate injury of tunica media in the presence of SO2 at 14 mg/m 3 . These suggest that SO2 can activate the KATP and BKCa channels by upregulating the expression of Kir6.1, Kir6.2, SUR2B, BKCa α, and BKCa β1, while inhibit the L-Ca 2+ channels by downregulating the expression of Cav 1.2 and Cav 1.3 in rat aortas. The molecular mechanism of SO2 -induced vasorelaxant effect might be linked to the changes in expression of these channel subunits, which plays an important role in the pathogenesis of SO2 -associated cardiovascular diseases.